2018
DOI: 10.1039/c7ta09001c
|View full text |Cite
|
Sign up to set email alerts
|

MXenes/graphene heterostructures for Li battery applications: a first principles study

Abstract: Heterostructure made of MXenes and graphene enhances the Li storage and increases the stability of the system for its application in a promising Li-ion battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(191 citation statements)
references
References 54 publications
12
176
2
1
Order By: Relevance
“…Computational studies of MXene/graphene heterostructures (where graphene and MXene layers stack alternately) have found that graphene is able to prevent restacking in scandium, titanium and vanadium M 2 CT X MXenes, and enhance mechanical stiffness, Li adsorption strength, and electric conductivity without compromising on Li diffusive mobility. Ti 2 CO 2 /graphene and V 2 CO 2 /graphene heterostructures exhibit the strongest Li binding energies (−1.43 eV at 1.49 V and −1.78 eV at 1.93 V respectively), and are predicted to swell no more than 5 % upon lithiation . Experimental studies have seen the development of an rGO/Ti 3 C 2 T X electrode made by filtration of a mixed colloid, and a range of 3D, porous rGO/Ti 3 C 2 T X foams made using hydrazine GO reduction .…”
Section: Li‐ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational studies of MXene/graphene heterostructures (where graphene and MXene layers stack alternately) have found that graphene is able to prevent restacking in scandium, titanium and vanadium M 2 CT X MXenes, and enhance mechanical stiffness, Li adsorption strength, and electric conductivity without compromising on Li diffusive mobility. Ti 2 CO 2 /graphene and V 2 CO 2 /graphene heterostructures exhibit the strongest Li binding energies (−1.43 eV at 1.49 V and −1.78 eV at 1.93 V respectively), and are predicted to swell no more than 5 % upon lithiation . Experimental studies have seen the development of an rGO/Ti 3 C 2 T X electrode made by filtration of a mixed colloid, and a range of 3D, porous rGO/Ti 3 C 2 T X foams made using hydrazine GO reduction .…”
Section: Li‐ion Batteriesmentioning
confidence: 99%
“…Ti 2 CO 2 /graphene and V 2 CO 2 /graphene heterostructures exhibit the strongest Li binding energies (À 1.43 eV at 1.49 V and À 1.78 eV at 1.93 V respectively), and are predicted to swell no more than 5 % upon lithiation. [82,83] Experimental studies have seen the development of an rGO/Ti 3 C 2 T X electrode made by filtration of a mixed colloid, [84] and a range of 3D, porous rGO/ Ti 3 C 2 T X foams made using hydrazine GO reduction. [85] Most of these composites are comparable to pure Ti 3 C 2 T X in their cycling stability and the variation in capacity with rate, but they consistently show significantly higher absolute values of capacity.…”
Section: Carbon and Silicon Mxene Compositesmentioning
confidence: 99%
“…[87] In addition, the stability of the individual models depends on their values, functional groups and elemental composition. [96,99] The lattice strain of the MXene phase further improves its excellent mechanical properties. [98] In addition, the F and OH groups limit the material's retention of metal ions because the O group exhibits superior cohesion to the others.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…led to substantial research on graphene-based composites. [99] This composite can be synthesized by an in situ growth method [130] or ex situ mixing method. For example, in graphene/nanoparticle composites, the inserted nanoparticles are able to prevent the stacking of graphene nanofilms without decreasing the large surface area or diminishing their electrical properties.…”
Section: Mxene-graphene Compositesmentioning
confidence: 99%
See 1 more Smart Citation